1964
DOI: 10.1037/h0047689
|View full text |Cite
|
Sign up to set email alerts
|

The origin of self-criticism.

Abstract: The learning of self-criticism is represented as the prototype of a form of internalization in which the child replicates certain components of the punishments to which it has been previously exposed. The stimulus properties of these components, first presented in the responses of a model, attain reinforcement value when they come to operate as signals for attenuation of the child's anticipatory anxiety. The effects of a variety of experimental socialization paradigms are combined with an analysis of naturalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 57 publications
0
35
0
1
Order By: Relevance
“…The idea of two conscience components is not new (e.g.. Burton, Maccoby, & Allinsmith, 1961;Hoffman, 1970a;Maccoby, 1980;Radke-Yarrow et al, 1968;Sears, Rau, &c Alpert, 1965). The emotions of fear, deviation anxiety, and guilt were central in the psychoanalytic and neo-Hullian models and in newer approaches to moral development (Aronfreed, 1964;Aronfreed & Reber, 1965;Hoffman, 1970aHoffman, , 1983. Behavioral control has been implied in social-learning and cognitive theories of moral development (Rest, 1983, Component IV).^ However, they have been treated as different foci rather than elements of an integrative framework.…”
Section: The Present Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of two conscience components is not new (e.g.. Burton, Maccoby, & Allinsmith, 1961;Hoffman, 1970a;Maccoby, 1980;Radke-Yarrow et al, 1968;Sears, Rau, &c Alpert, 1965). The emotions of fear, deviation anxiety, and guilt were central in the psychoanalytic and neo-Hullian models and in newer approaches to moral development (Aronfreed, 1964;Aronfreed & Reber, 1965;Hoffman, 1970aHoffman, , 1983. Behavioral control has been implied in social-learning and cognitive theories of moral development (Rest, 1983, Component IV).^ However, they have been treated as different foci rather than elements of an integrative framework.…”
Section: The Present Modelmentioning
confidence: 99%
“…Often, the focus has been on the prohibitive aspectdiscomfort associated with wrongdoing and the resulting avoidance of forbidden acts. Consequently, investigators examined affective processes, such as deviation anxiety, guilt, remorse, self-criticism, discomfort, and anxiety associated with transgressions (Aronfreed, 1964;Aronfreed & Reber, 1965;Dienstbier, Hillman, Lehnhoff, Hillman, & Valkenaar, 1975;Hoffman, 1975), and self-control capacities, such as resistance to temptation .…”
mentioning
confidence: 99%
“…Maccoby (1959) has suggested that parental behavior is attended to, rehearsed, and then reproduced by the child under conditions similar to those which originally evoked the parental response (e.g., following a deviant act). Research findings have generally substantiated Maccoby's formulation; for example, Aronfreed (1963Aronfreed ( , 1964 has demonstrated that children reproduce an adult's criticism of their behavior if the critical comments have been paired with the termination of an aversive event. Grusec (1966) has found that withdrawal of love or material reinforcers contingent upon transgression in a game would also facilitate children's verbal self-criticism.…”
Section: University Of Utahmentioning
confidence: 91%
“…In other studies of self-criticism, extensive verbal probes have been used to elicit reproduction of the critical label (Aronfreed, 1963(Aronfreed, , 1964Grusec, 1966). Certainly further research is needed to isolate the variables controlling imitation of different types of behavior.…”
Section: Self-esteem Ratingsmentioning
confidence: 98%
“…This is an extremely provocative article suggesting a number of hypotheses which should be put to experimental test. Aronfreed (1964) examined the question of how self-critical responses following a transgression are learned. One interpretation suggests that the child learns such responses by imitating a generally nurturant parent or adult who emits such responses at the time of punishment.…”
Section: Social Punishmentmentioning
confidence: 99%